Specific Heat Capacity Estimations for Biologically and Medicinally Important Compounds: Lidocaine Hydrochloride, Clove Oil and β-Piperine Using the DSC Technique - Gupta, Gaurav; Shaikh, Vasim; Kalas, Sachin; Patil, Kesharsingh (Current Physical Chemistry, 2021)
Aim: To study the specific heat capacity for biologically and medicinally important compounds, namely, lidocaine hydrochloride, clove oil and beta-Piperine using the DSC technique. Background: One of the main problems in the science of medicine is the application of drug molecules with limited solubility in water and in biofluids. Solubility is related to the chemical potential of the solutes involved, which imparts free energy avenues, a necessary requirement for equilibrium processes. The convincing solutions for solving this issue are the utilization of ionic liquids as a drug. Lidocaine is the most widely utilized intraoral injected dental anesthetic prior to performing painful medical procedures. Besides that, lidocaine hydrochloride is a salt, having a melting point of 76°C (349 K) and behaves as an ionic liquid after melting. Clove oil and β-piperine are very well-known naturally occurring medicinal compounds having a broad spectrum of applications. Objective: To study the thermal gravimetry analysis behaviour for lidocaine hydrochloride, clove oil and β-piperine. To compute specific heat capacity at constant pressure, as a function of temperature for the studied systems. Methods: In the present communication, the studies of Thermal Gravimetry Analysis (TGA) and Differential Scanning Calorimetry (DSC) for these compounds are described. Results: The data of heat flow have been utilized to obtain specific heat capacity (Cp) values for lidocaine hydrochloride, clove oil and β-piperine over a temperature range between 75°C (348 K) and 155°C (428 K) based upon the methodology we have developed. Conclusion: LC•HCl behaves as an ionic liquid between 76 and 230°C (349 and 503 K). Clove oil shows lower specific heat capacity values and is similar to other organic aromatic compounds while piperine exhibits comparative high specific heat capacity values indicating possibilities of intramolecular hydrogen bonding, which is generally not affected by temperature.
Keywords: clove oil